A Phase II Study of Durvalumab in Combination with Tremelimumab in Patients with Rare Cancers. (8th May 2021) - Edenfield, William Jeffery; Chung, Ki; O'Rourke, Mark; Cull, Elizabeth; Martin, Julie; Bowers, Heather; Smith, Wesley; Gluck, William Larry
Abstract: Lessons Learned: Disease control with signals of response were demonstrated, which should lead to future validating clinical trials using checkpoint inhibitors in this underserved rare malignancy population. Although the study of single types of rare cancers is practically challenging, clinical trial designs that aggregate such patients into cohorts treated similarly are feasible, even in the community setting. Background: Patients with rare cancers are an underserved population with limited access to clinical trials aside from phase I trials in the refractory setting. Treatment of these patients is often based on collections of anecdotes and small denominator review articles. Despite broad evidence of efficacy of combined immune checkpoint blockade across multiple tumor types, patients with rare tumors have not been afforded the opportunity for these therapies. Methods: A phase II, investigator‐initiated, single institution trial using durvalumab (1, 500 mg every [Q]4 weeks × 13) and tremelimumab (75 mg Q4 weeks × 7, then Q12 weeks × 2) is reported. The population included 50 patients with advanced rare solid tumors (incidence <6/100, 000 per year). The phase II dose and safety profile were defined in prior phase I trials. All patients had exhausted standard therapy options and all had received at least one prior line of systemic therapy ( n  = 49) unless a standard treatment option did not exist ( n  = 1). Results: A complete response was demonstrated in one patient with anal cancer. Striking partial responses were seen in four patients. Prolonged disease stability was noted in 18 patients. Thirteen patients experienced disease progression. Patients were considered unevaluable if unable to initiate therapy ( n  = 6) or unable to complete two cycles of therapy ( n  = 8). In all cases, patients were unevaluable because of clinical deterioration. The toxicity profile paralleled prior published studies. Toxicities were manageable and without new signals. There were two events of grade 4 immune‐mediated hepatitis and one death from pneumonitis. Conclusion: This single‐cohort basket trial demonstrated clinical activity from combined checkpoint blockade in 23 of the 36 evaluable patients. Patients with rare cancers, not eligible for immunotherapy via conventional clinical trial mechanisms, should be considered for this therapy through compassionate use, further clinical trials, and national registry programs.